On some methods for solving the problem of power distribution of data transmission channels taking into account fuzzy constraints on consumption volumes - Євген Івохін; Лариса Аджубей; Петро Ваврик; Михайло Махно (Sistemnì Doslìdženâ ta Informacìjnì Tehnologìï, 2022)
The article deals with the mathematical formulation of the problem of optimal distribution of the power of data transmission channels in information and computer networks with a three-level architecture and fuzzy restrictions on consumption volumes. An efficient algorithm has been developed for solving the problem, the peculiarity of which is the inability to meet the end user’s needs at the expense of the resources of different suppliers. A standard solution method based on a fuzzy optimization problem of mathematical programming is considered. A constructive variant of finding a solution based on the backtracking method is proposed. Computational experiments have been carried out. The developed approach was used to determine the optimal configuration of a three-level information and computer network with a given number of communication servers.